MULHERES QUE RIMAM: NARRATIVAS DO MELANINA MC’S COMO INSTRUMENTO DE RETERRITORIALIZAÇÃO - Sampaio, Carolina Ofranti (2020)
This thesis analyzes the female reterritorializations in the Espírito Santo s rap, having as object of study the first and only album of the group Melanina MC s: Female System. Representing one of the elements of the Hip Hop Movement, which has emerged as